EDUKASI TEKNIK KNEE TO CHEST EXERCISE UNTUK MENGATASI NYERI PUNGGUNG BAWAH - Ika Guslanda Bustam (Khidmah, 2022)
One of the managements of pain conditions caused by low back pain (Low Back Pain) is physiotherapy. The treatment that can be given is the Knee to Chest Exercise technique. The objectives of this community service are: 1) To provide health education about the Knee to Chest Exercise technique to treat low back pain; 2) The public knows the benefits and effects of the Knee to Chest Exercise technique; and 3) The community is able to perform the Knee to Chest Exercise technique. The method was used in this activity by presenting material to increase knowledge using power points and leaflets as well as direct demonstrations so that participants are skilled in performing the Knee to Chest Exercise technique. This activity was attended by women with an age range of 50 – 78 years old. The results of the evaluation revealed that there was a decrease in unmovement pain from Visual Analogue Scale (VAS) 4 to VAS 2, motion pain from VAS 8 to VAS 5, and tenderness from VAS 8 to VAS 6. In addition, each participant was also able to understand, explain definition, causes, signs and symptoms, and how to deal with low back pain.